A general strategy for tailoring upconversion luminescence in lanthanide-doped inorganic nanocrystals through local structure engineering. Issue 19 (8th May 2018) - Fu, Huhui; Peng, Pengfei; Li, Renfu; Liu, Caiping; Liu, Yongsheng; Jiang, Feilong; Hong, Maochun; Chen, Xueyuan
Abstract : We report a series of Yb 3+ /Er 3+ co-doped alkaline zirconium fluoride nanocrystals to thoroughly understand the origin underlying the local-structure-dependent upconversion luminescence. Abstract : A local structure around lanthanide (Ln 3+ ) emitters in Ln 3+ -doped upconversion nanocrystals (UCNCs) is of fundamental importance in tailoring their upconversion luminescence (UCL) features. However, a general strategy responsible for the local-structure-dependent UCL in Ln 3+ -doped UCNCs has not been conclusively established to date. Herein, we report a new class of alkaline zirconium fluoride-based Yb 3+ /Er 3+ co-doped UCNCs featuring a diversity of crystallographic structures for Ln 3+ ion doping, which thereby allow us to thoroughly understand the origin underlying the local-structure-dependent UCL of the Er 3+ ion for the first time. We reveal that the high-symmetry crystal lattice of Yb 3+ /Er 3+ co-doped UCNCs may incur the large UCL red-to-green intensity ratio of Er 3+ regardless of their identical elemental compositions. In combination with the first-principles calculations, we show that such local-structure-dependent UCL of Er 3+ is primarily due to the varied electronic band structures induced by the Yb 3+ /Er 3+ doping in different crystallographic structures of alkaline zirconium fluorides. These findings may open up a new avenue for constructing high-quality UCNCs with a tailored UCL profile and lifetime for diverse applications.